Visual Merchandising in The Showroom of Mobile Operators on The Polish Market - Mariusz WOŹNIAKOWSKI (Communications of International Proceedings, 2022)
The main task of Visual Merchandising (VM) is to create the perfect shopping conditions for the customer, provide the products with the best possible exposure, and thus generate the highest possible turnover. This task is not an easy art. It requires regular work with the goods and constant attention to the details of the visual exhibition. One may be tempted to say that an effective VM in the fight for a customer can do more than many talented salespeople. Thanks to the knowledge of the rules of Visual Merchandising, you can perfectly communicate with the customer and influence his purchasing decisions. The use of techniques for creating commercial space allows you to create an environment conducive to friendly and effective shopping, thanks to which customers will be more likely to come back. In the literature on the subject, the most attention is paid to the issue of VM concerning commercial networks, mainly supermarkets and clothing stores. However, an effective VM will also have an impact on the competitiveness of points where services are mainly sold along with complementary products. This type of entity undoubtedly includes the branches of telecommunications operators. This publication focuses on the presentation and comparison of the VM rules used in selected showrooms of operators active in the Polish telecommunications market. The comparison was made based on the author's research. Research has shown that each of the stores of the brands of mobile operators in Poland, thanks to the use of a color scheme that is unique to it, allows for trouble-free identification among customers. It is thanks to the colors that the operators' stationary stores create their own, unique, distinguishing visual identity from the competition. The elements of visual merchandising, which are particularly emphasized in stationary stores, are: lighting, interior colors and furnishings, consistency of advertisements and other promotion instruments of offers, arranging window displays and displays with electronic devices.
Keywords: Merchandising; visual merchandising; mobile operator; telecommunications operator.